Sarcopenia in chronic obstructive pulmonary disease: A study of prevalence and associated factors in the Southeast Asian population. (August 2018) - Limpawattana, Panita; Inthasuwan, Pratchaya; Putraveephong, Siraphong; Boonsawat, Watchara; Theerakulpisut, Daris; Sawanyawisuth, Kittisak
Chronic obstructive pulmonary disease (COPD) has been described as a systemic disease. Sarcopenia is one of the systemic effects that is related to several adverse outcomes. The objectives of this study were to estimate the prevalence of sarcopenia and to determine the factors associated with sarcopenia in COPD patients in Southeast Asia. This was a cross-sectional study of COPD patients who attended a COPD clinic from May 2015 to December 2016. Baseline characteristics were collected and dual-energy X-ray absorptiometry was used to measure skeletal muscle mass. Handgrip strength was used to assess muscle strength, and as a measurement of physical performance, the 6-min walk distance was used. One hundred and twenty-one participants were recruited. Most of them were men (92.6%). Prevalence of sarcopenia was 24% (29 cases). Independent factors associated with sarcopenia were age ≥ 75 years (adjusted odds ratio (AOR) 13.3, severity of COPD (AOR 19.2 and 13.4 for moderate and severe COPD), Modified Medical Research Council (MMRC) scale (AOD 1.9), and obesity (AOR 0.04). Sarcopenia affects about one-quarter of COPD patients. Age, severity of COPD, MMRC scale, and BMI status were the factors associated with sarcopenia.